A study on the effects of electromagnetic coupling mechanisms in the event of an indirect lightning strike near photovoltaic arrays. Issue 4 (1st February 2023) - Hernández, Jesús De La Casa; Sutil, Francisco José Sánchez; Petrarca, Carlo; Formisano, Alessandro
Abstract: Indirect lightning strikes hitting near photovoltaic installations are much more frequent than direct hits, and can generate overvoltage in their electric circuitry. The authors developed a method to estimate the induced overvoltage on single photovoltaic modules. Using a model of the whole array also including Inter‐Module Coupling Mechanisms (IMCMs), a new approach to estimate overvoltage induced on full arrays is presented in this paper. The procedure first estimates lumped parameters, modelling either the coupling between the lightning channel and each module in the array or between each couple of modules in array. Several circuital simulations are then run using suitable equivalent circuits. The aim is to consider different array configurations and groundings schemes. This allows extracting the most relevant configuration parameters influencing overvoltage/overcurrent. Results show that the groundings scheme impacts negligibly, but the single module electric stress is decreased by 35% in the case of ungrounded configurations. Among the considered array configurations, the honey‐comb and total cross‐tied showed the smallest impact on overvoltage. Statistical analysis on random LC tortuous geometry leads to a non‐negligible rise of overvoltage peak values, up to 24%. Finally, the relevance of different IMCMs is analysed, showing a strong impact just on frame‐ground voltages and currents.